The Infeksi Virus Corona 2019 (COVID-19) pada Wanita Hamil : Analisa Pustaka Mekanisme Infeksi dan Pengaruh Pengobatan terhadap Kehamilan - Hidayah, Nurul; Indriani, Susan; Rahmatika, Farida (Essence of Scientific Medical Journal; Vol 19 No 1 (2021): Volume 19 No. 1 (Januari - Juni 2021) Essential: Essence of Scientific Medical Journal, 2021)
ABSTRACT Introduction: Coronavirus is a virus that affects the respiratory tract. It causes mild to severe symptoms such as coughing, shortness of breath / risk of apneu. There are many studies that are relate to therapy that can be used to prevent and cure coronavirus infection. Patients with severe symptoms can be given chloroquine; however, it is not known yet the infection mechanism and effect of using chloroquine on pregnant patients with corona virus infection. Discussion: SARS-CoV-2 is an RNA virus that causes coronavirus disease (COVID-19). The virus was first spread in Wuhan, China, through bats. It can penetrate into the human respiration system by contacting directly with infected animals. Pregnant women and their fetuses are a high-risk population which are easily infected by coronavirus due to their low immune defenses in the body. In this case, complications caused by coronavirus infection are including IUGR, prematurity, low birth weight (LBW), and abortion. For now, Chloroquine is the most recommended treatment for pregnant women with coronavirus infection. Chloroquine is a bioactive agent that can fight various RNA viruses including SARS-CoV-2 by inhibiting viral replication through inhibition of quinone reductase-2. The use of chloroquine drugs (150 mg-500 mg) can form protection for the fetus. Conclusion: Pregnant women and their fetuses become one of the high-risk populations who are easily affected by coronavirus infection. The important thing to do is to take medicine as one of the steps to minimize worsening conditions. Chloroquine drug has become the right choice for the treatment of coronavirus infection in pregnant women. No serious side effects were found in pregnant women or newborns after giving chloroquine therapy. Keywords: Coronavirus disease 2019 (COVID-19), Chloroquine, pregnancy